Urban Growth Evaluation by Coupling Descriptive Analysis and Zipf’s Rank-Size Model in Parakou (Benin) - LANMANDJEKPOGNI, PAUL; Codo, Francois de Paule; YAO, Benjamin (My University, 2019)
Parakou occupies a strategic place in the socio-economic development of Benin due to its geographical position. Based on the Urban Land Registry data, and census data from the National Institute of Statistics and Applied Economics coupling with the statistical description and adjustment to the distribution Zipf rank-size model, allowed us to describe the urban hierarchy on the scale of Parakou localities over the period 1979 to 2013. The changes in densities of population occupation per decade show a tendency to sprawl from the 2000s and linear and quadratic adjustments are satisfactory (linear: 0.81≤ R² ≤ 0.95 and quadratic: 0.95 ≤ R2 ≤ 0.98) and significant at 1% (P-value = 0.000) to 88%. The linear coefficients of Pareto are continuously decreasing (ǀαǀ = 1.749 to ǀαǀ = 0.831 between 1979 and 2002), and reflect that the weight of big cities keeps an influence on small and medium-sized cities over this period, while a slight increase was observed in the courtyard of the decade from 2002 to 2013 (ǀαǀ = 0.861 in 2013) and shows the effect of the creation of new districts with the gradual loss of the influence of the old districts of the central core. The results suggest that population growth of the city is occurred with urban sprawl controlled by exogenous factors of infrastructures or land type. Managements of spatial planning structures are then arrested in the guidelines to provide land for the human impacts control on natural resources of watersheds
Keywords: Urban; Growth; Parakou; Spatial Planning